MRI Brain In Case Non-Hemmoragic STROKE At Gatot Soebroto Army Central Hospital (RSPAD): English - Muh. Saqri Al Faruq; Anwar, Khairil; Apriantoro, Nursama Heru; P.I Patra (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2024)
Non-hemorrhagic stroke caused by thrombus and embolism, occurs due to decreased blood flow to certain places in the brain through the process of stenosis. Identification of the pathophysiology of non-hemorrhagic stroke due to stenosis is important in patient management, especially in providing appropriate therapy. Cerebral lesions visualized on MRI show tissue damage due to reduced blood flow to the brain, which deprives brain cells of oxygen and essential nutrients. The research was carried out from 03 to 29 October 2022 at Gatot Soebroto Army Hospital, with 1 sample analysis of a 70-year-old man with complaints of partial paralysis of the left side of the body covering the arms and legs, the study was carried out using descriptive qualitative methods with a case study approach. The results of MRI Brain imaging using a complete Head Protocol consisting of sequences T1, T2, FLAIR, DWI, ASL 3d_Tra_Iso, TOF MRA, MRV and Carotis, and SWI showed acute infarction, multiple lacunar infarction, cerebral atrophy, hypoperfusion. Conclusion: MRI examination of the head using a complete head protocol at Gatot Soebroto Hospital is very effective for assessing non-hemorrhagic stroke.